Fast ion conductor coated P2 / O3 composite phase sodium ion layered positive electrode material as well as preparation and application thereof

By using NASICON type Na5Ti2Si2PO13 material as the cladding layer, the P2/O3 composite phase material was modified, and the fast ion conductor-coated NaiMnxCoyNizM1mM2nM3pO2@NTSP material was constructed, which solved the problems of interface instability and poor sodium conduction performance, and achieved the goal of achieving the problem of The long cycle stability and electrochemical performance of the material are improved.

CN119447250APending Publication Date: 2025-02-14XIAMEN UNIV OF TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411597317.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-11
Publication Date
2025-02-14

AI Technical Summary

Technical Problem

The existing P2/O3 composite phase sodium ion layered cathode materials have problems such as interfacial instability and poor sodium conduction performance.

Method used

Using NASICON type Na5Ti2Si2PO13 (NTSP) material with a stable P-O skeleton and an open three-dimensional Na+ channel as the cladding layer, the P2/O3 composite phase NaiMnxCoyNizM1mM2nM3pO2 material was surface coated and modified to construct a fast-ion conductor-coated NaiMnxCoyNizM1mM2nM3pO2@ NTSP material.

Benefits of technology

It effectively reduces the side reactions of the electrode/electrolyte interface, improves the long cycle structure and electrochemical stability of the material, solves the problem of interface instability, and improves sodium conduction performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119447250A_ABST
    Figure CN119447250A_ABST
Patent Text Reader

Abstract

The invention discloses a fast ion conductor coated P2 / O3 composite phase sodium ion layered positive electrode material and a preparation method thereof, the preparation method comprises the following steps: firstly preparing a P2 / O3 composite phase material NaiMnxCoyNizM1mM2nM3pO2 by adopting a combustion method, and then coating the surface of the P2 / O3 composite phase material with Na5Ti2Si2PO13 (NTSP) by adopting a sol-gel method to prepare the fast ion conductor coated P2 / O3 composite phase sodium ion layered positive electrode material, m2 is a trivalent metal element for doping and substituting Co site, and M3 is a divalent metal element for doping and substituting Ni site. When the material is used as a positive electrode material for preparing a sodium ion battery, electrolyte erosion and interface side reaction can be reduced, the electrochemical performance of the material is improved, and the problems that an existing P2 / O3 composite phase material is unstable in interface and poor in sodium conduction performance are effectively solved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of sodium ion battery materials, and particularly relates to a fast ion conductor material Na5Ti2Si2PO 13 (NTSP) coated P2 / O3 composite phase Na i Mn x Co y Ni z M1 m M2 n M3 p O2 layered material, its preparation method and its application as a positive electrode of a sodium ion battery. Background Art

[0002] Sodium ion batteries have the advantages of rich resources and low raw material costs, and are one of the most promising alternative technologies for next-generation large-scale energy storage. Currently, the positive electrode materials of sodium ion batteries mainly include transition metal layered oxides, Prussian blue, and phosphates. Among them, transition metal layered oxides are considered to be strong candidates for low-cost, high-capacity energy storage batteries due to their easy synthesis, adjustable composition, and high capacity density, and have received extensive research attention.

[0003] Currently, the most studied Na x TMO2 materials are O3 type (0.7 < x <= 1) and P2 type (x < 0.7), where the letters respectively represent Na + occupying the coordination environments of octahedrons and triangular prisms, and the numbers are the number of repeated sodium layers in a single unit cell. The P2 phase and O3 phase materials each have their own advantages. The O3 type material has a higher theoretical capacity due to its higher sodium content, however, its higher ion diffusion energy barrier restricts the improvement of its rate performance. On the contrary, the P2 type sodium ion layered material has a lower sodium ion diffusion energy barrier and better structural stability, however, its lower sodium content results in a lower theoretical specific capacity. The P2 / O3 composite phase material can better couple the advantages of high rate and long cycle of the P2 phase and high capacity of the O3 phase. Existing research shows that the P2 / O3 composite phase (Na i Mn x Co y Ni z M1 m M2 n M3 p O2) material has good cycle performance and rate performance. However, during the sodiation / desodiation process, due to the volume strain generated by the phase change, and in the high voltage range Ni 4+The strong oxidizing property of the cathode material will still lead to the problem of unstable electrode / electrolyte interface, and the long cycle stability of the cathode material is not utilized. To address the interface stability problem caused by phase change, the most effective strategy is to use surface modification to prevent electrolyte erosion. The main surface modification methods currently used include Al2O3, MgO and carbon coating. However, these surface modification layers have poor sodium ion conductivity and are not conducive to the deintercalation of sodium ions in the material.

[0004] In view of the interface stability problem that still exists in P2 / O3 composite phase sodium ion layered cathode materials, the present invention adopts a PO with a stable skeleton and an open three-dimensional Na + Channeled NASICON-type Na5Ti2Si2PO 13 (NTSP) material as a coating layer, P2 / O3 composite phase Na i Mn x Co y Ni z M1 m M2 n M3 p O2 materials were surface-coated to construct Na i Mn x Co y Ni z M1 m M2 n M3 p O2@NTSP material can achieve interface modification, reduce electrolyte corrosion and interface side reactions, and effectively improve the electrochemical performance of the material. Summary of the invention

[0005] The purpose of the present invention is to provide a fast ion conductor coated with Na5Ti2Si2PO 13 (NTSP) P2 / O3 composite phase Na i Mn x Co y Ni z M1 m M2 n M3 p The preparation method of O2 layered material and its application in the positive electrode of sodium ion battery can effectively solve the problems of interface instability and poor sodium conductivity of existing P2 / O3 composite phase materials.

[0006] To achieve the above object, the present invention adopts the following technical solution: A fast ion conductor coated P2 / O3 composite phase layered material, which is specifically composed of Na5Ti2Si2PO 13 (NTSP) coated in P2 / O3 composite phase Na i Mn xCo y Ni z M1 m M2 n M3 p O2 surface composition; wherein, M1 is a tetravalent metal element doped to replace the Mn position, M2 is a trivalent metal element doped to replace the Co position, and M3 is a divalent metal element doped to replace the Ni position; 0.72≤i≤0.8, 0.1≤x≤0.3, 0.1≤y≤0.4, 0.1≤z≤0.3, 0.03<m≤0.15, 0.03<n≤0.15, 0.03<p≤0.15, and x+y+z+m+n+p=1.

[0007] Furthermore, M1 is specifically selected from one or more of Ti, Zr, and Si; M2 is specifically selected from one or more of Fe, Cr, and Al; and M3 is specifically selected from one or more of Mg, Cu, and Zn.

[0008] Furthermore, Na5Ti2Si2PO 13 In Na i Mn x Co y Ni z M1 m M2 n M3 p The coating amount of O2 surface is 1-5wt%.

[0009] The preparation of the P2 / O3 composite layered material coated with a fast ion conductor is to firstly prepare the P2 / O3 composite layered material Na by a combustion method. i Mn x Co y Ni z M1 m M2 n M3 p O2, and then coated with Na5Ti2Si2PO4 on its surface by sol-gel method. 13 ; It specifically includes the following steps: (1) Press Na first i Mn x Co y Ni z M1 m M2 n M3 p The Na source, Mn source, Co source, Ni source, M1 source, M2 source and M3 source were weighed in a stoichiometric ratio of O2, and then stirred and mixed with sucrose and deionized water to obtain a mixed solution, and then the mixed solution was heated and stirred until it became a syrup, and then calcined at a high temperature in air to obtain a P2 / O3 composite layered material Na i Mn xCo y Ni z M1 m M2 n M3 p O2; (2) According to Na5Ti2Si2PO 13 The stoichiometric ratio of C 16 H 36 O4Ti and C8H 20 O4Si was dissolved in ethanol to obtain solution A, and Na2CO3 and NH4H2PO4 were dissolved in deionized water to obtain solution B; (3) Add P2 / O3 composite layered material Na into solution A. i Mn x Co y Ni z M1 m M2 n M3 p O2, then slowly add solution B, heat at 70 °C with stirring to evaporate to dryness, and then dry in a vacuum drying oven at 110 °C for 12 h; (4) The dried sample in step (3) is placed in a muffle furnace for calcination to obtain Na5Ti2Si2PO 13 Coated P2 / O3 composite phase Na i Mn x Co y Ni z M1 m M2 n M3 p O2 layered materials.

[0010] Furthermore, the Na source, Mn source, Co source, Ni source, M2 source and M3 source in step (1) are all nitrates of corresponding elements; and the M1 source is one or more of titanium oxide, zirconium oxide and silicon oxide.

[0011] Furthermore, the amount of sucrose used in step (1) is converted to 3.0 g per 1 gram of P2 / O3 composite layered material; the amount of deionized water used is converted to 38.4 mL per 1 gram of P2 / O3 composite layered material.

[0012] Furthermore, the high temperature calcination in step (1) is firstly kept at 350°C for 0.5 h, then ground in a mortar for 1 h, then heated to 500°C, kept for 3 h, and finally heated to 800-900°C, kept for 10-24 h.

[0013] Furthermore, the calcination in step (4) is carried out by heating the temperature from room temperature to 350°C at a rate of 2°C / min, keeping the temperature for 5 hours, and then heating the temperature to 900°C and keeping the temperature for 6 hours.

[0014] The P2 / O3 composite phase Na i Mn x Co y Ni z M1 m M2 n M3 p O2 layered materials can be used as positive electrode materials for the preparation of sodium ion batteries.

[0015] The significant advantages of the present invention are: The present invention adopts a PO-based structure with a stable PO skeleton and an open three-dimensional Na + The fast ion conductor NTSP material of the channel is used as the coating layer to construct the Na i Mn x Co y Ni z M1 m M2 n M3 p O2@NTSP material overcomes the traditional coating layer Na + The problem of poor ion transport performance is solved, and the side reactions at the electrode / electrolyte interface are effectively reduced, and the structural and electrochemical stability of the material under long-term cycling are improved, thereby solving the problem of the existing P2 / O3 composite phase Na i Mn x Co y Ni z M1 m M2 n M3 p O2 materials have the problem of interface instability. BRIEF DESCRIPTION OF THE DRAWINGS

[0016] Figure 1 The Na prepared in Example 1 0.78 Mn 0.4 Co 0.1 Ni 0.2 Ti 0.1 Fe 0.1 Cu 0.1 SEM image of O2@1NTSP material.

[0017] Figure 2 The Na prepared in Example 1 0.78 Mn 0.4 Co 0.1 Ni 0.2 Ti 0.1 Fe 0.1 Cu0.1 Field emission scanning electron microscope image and EDS element distribution map of O2@1NTSP material.

[0018] Figure 3 The Na prepared in Example 1 0.78 Mn 0.4 Co 0.1 Ni 0.2 Ti 0.1 Fe 0.1 Cu 0.1 XRD pattern of O2@1NTSP material.

[0019] Figure 4 The Na prepared in Example 1 0.78 Mn 0.4 Co 0.1 Ni 0.2 Ti 0.1 Fe 0.1 Cu 0.1 Electrochemical performance diagram of O2@1NTSP material, where , where a is the material at 24 mA g -1 The first cycle charge and discharge curve under current, b is the material at 24 mA g -1 Long cycle performance diagram under current.

[0020] Figure 5 The Na prepared in Example 2 0.78 Mn 0.4 Co 0.1 Ni 0.2 Ti 0.1 Fe 0.1 Cu 0.1 SEM image of O2@2.5NTSP material.

[0021] Figure 6 The Na prepared in Example 2 0.78 Mn 0.4 Co 0.1 Ni 0.2 Ti 0.1 Fe 0.1 Cu 0.1 XRD pattern of O2@2.5NTSP material.

[0022] Figure 7 The Na prepared in Example 2 0.78 Mn 0.4 Co 0.1 Ni 0.2 Ti 0.1 Fe 0.1 Cu 0.1 Electrochemical performance diagram of O2@2.5NTSP material, where a is the material at 24 mA g-1 The first cycle charge and discharge curve under current, b is the material at 24 mA g -1 Long cycle performance diagram under current.

[0023] Figure 8 The Na prepared in Example 3 0.78 Mn 0.4 Co 0.1 Ni 0.2 Ti 0.1 Fe 0.1 Cu 0.1 SEM image of O2@5NTSP material.

[0024] Fig. 9 The Na prepared in Example 3 0.78 Mn 0.4 Co 0.1 Ni 0.2 Ti 0.1 Fe 0.1 Cu 0.1 XRD pattern of O2@5NTSP material.

[0025] Fig.10 The Na prepared in Example 3 0.78 Mn 0.4 Co 0.1 Ni 0.2 Ti 0.1 Fe 0.1 Cu 0.1 Electrochemical performance diagram of O2@5NTSP material, where a is the material at 24 mA g -1 The first cycle charge and discharge curve under current, b is the material at 24 mA g -1 Long cycle performance diagram under current.

[0026] Fig.11 The Na prepared in the comparative example 0.78 Mn 0.4 Co 0.1 Ni 0.2 Ti 0.1 Fe 0.1 Cu 0.1 SEM image of O2 material.

[0027] Fig.12 The Na prepared in the comparative example 0.78 Mn 0.4 Co 0.1 Ni 0.2 Ti 0.1 Fe 0.1 Cu 0.1 XRD pattern of O2 material.

[0028] Fig.13 The Na prepared in the comparative example 0.78 Mn 0.4 Co 0.1 Ni 0.2 Ti 0.1 Fe 0.1 Cu 0.1 Electrochemical performance diagram of O2 material, where a is the material at 24 mA g -1 The first cycle charge and discharge curve under current, b is the material at 24 mA g -1 Long cycle performance diagram under current. DETAILED DESCRIPTION

[0029] A fast ion conductor coated P2 / O3 composite phase layered material, which is specifically composed of Na5Ti2Si2PO 13 (NTSP) coated in P2 / O3 composite phase Na i Mn x Co y Ni z M1 m M2 n M3 p O2 surface composition; wherein, M1 can be selected from one or more of Ti, Zr, Si; M2 can be selected from one or more of Fe, Cr, Al; M3 can be selected from one or more of Mg, Cu, Zn; 0.72≤i≤0.8, 0.1≤x≤0.3, 0.1≤y≤0.4, 0.1≤z≤0.3, 0.03<m≤0.15, 0.03<n≤0.15, 0.03<p≤0.15, and x+y+z+m+n+p=1.

[0030] The preparation steps of the P2 / O3 composite phase material coated with a fast ion conductor are as follows: (1) Press Na first i Mn x Co y Ni z M1 m M2 n M3 pNaNO3, Mn(NO3)2, Co(NO3)2, Ni(NO3)2 and oxides of M1, nitrates of M2 and nitrates of M3 were weighed in a stoichiometric ratio of 1:1 and 1:1. Then sucrose and deionized water were added at 3.0 g / g (P2 / O3 composite layered material) and 38.4 mL / g (P2 / O3 composite layered material) respectively, and the mixture was stirred to obtain a mixed solution. The mixed solution was then heated and stirred until it became a syrupy state, and then kept at 350 °C in air for 0.5 h, then ground in a mortar for 1 h, and then the powder was calcined at 500 °C in air for 3 h, and then heated to 800-900 °C and kept warm for 10-24 h to obtain a P2 / O3 composite layered material Na i Mn x Co y Ni z M1 m M2 n M3 p O2; (2) According to Na5Ti2Si2PO 13 The stoichiometric ratio of C 16 H 36 O4Ti and C8H 20 O4Si was dissolved in ethanol to obtain solution A, and Na2CO3 and NH4H2PO4 were dissolved in deionized water to obtain solution B; (3) Add P2 / O3 composite layered material Na into solution A. i Mn x Co y Ni z M1 m M2 n M3 p O2, then slowly add solution B, heat at 70 °C and stir to evaporate to dryness, then dry the evaporated sample in a vacuum drying oven at 110 °C for 12 h; (4) The sample dried in step (3) was placed in a muffle furnace and heated from room temperature to 350°C at a rate of 2°C / min, kept at that temperature for 5 h, and then heated to 900°C and kept at that temperature for 6 h, thereby obtaining Na i Mn x Co y Ni z M1 m M2 n M3 p O2@xNTSP material (1≤x≤5).

[0031] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0032] Example 1Na 0.78 Mn 0.4 Co 0.1 Ni 0.2 Ti 0.1 Fe 0.1 Cu 0.1 Preparation of O2@1NTSP materials (1) According to Na 0.78 Mn 0.4 Co 0.1 Ni 0.2 Ti 0.1 Fe 0.1 Cu 0.1 O2, weigh 0.696 g NaNO3, 0.734 g Mn(NO3)2, 0.183 g Co(NO3)2, 0.347 g Ni(NO3)2, 0.242 g Fe(NO3)3, 0.19 g Cu(NO3)2, 0.08 g TiO2, 7.42 g sucrose and 94.9 mL deionized water, stir to obtain a mixed solution, then heat and stir the mixed solution in an oil bath until it is syrupy, finally calcined at 350 °C in air for 0.5 h, ground in a mortar for 1 h, and then calcined the powder at 500 °C in air for 3 h, and then calcined at 900 °C for 15 h to obtain P2 / O3 composite phase Na 0.78 Mn 0.4 Co 0.1 Ni 0.2 Ti 0.1 Fe 0.1 Cu 0.1 O2.

[0033] (2) 0.067 g C 16 H 36 O4Ti and 0.042g C8H 20 O4Si was dissolved in 15 mL of ethanol to obtain solution A; 0.0262 g of Na2CO3 and 0.0147 g of NH4H2PO4 were dissolved in 3 mL of deionized water to obtain solution B.

[0034] (3) Add 0.5 g of P2 / O3 composite phase Na 0.78 Mn0.4 Co 0.1 Ni 0.2 Ti 0.1 Fe 0.1 Cu 0.1 O2 material, then slowly add solution B, heat at 70 ℃ uniformly with stirring to evaporate to dryness, and then dry the evaporated sample in a vacuum drying oven at 110 ℃ for 12 h.

[0035] (4) The dried sample was heated from room temperature to 350 °C at a rate of 2 °C / min in a muffle furnace and calcined for 5 h, then heated to 900 °C and calcined for 6 h to obtain a P2 / O3 composite phase Na2O3 with a NTSP coating of 1 wt%. 0.78 Mn 0.4 Co 0.1 Ni 0. 2Ti 0.1 Fe 0.1 Cu 0.1 O2 material, denoted as Na 0.78 Mn 0.4 Co 0.1 Ni 0.2 Ti 0.1 Fe 0.1 Cu 0.1 O2@1NTSP.

[0036] The prepared Na 0.78 Mn 0.4 Co 0.1 Ni 0.2 Ti 0.1 Fe 0.1 Cu 0.1 O2@1NTSP material was tested by SEM, and the results are as follows Figure 1 As shown. Figure 1 It can be seen that smaller particles appear on the surface of the material and are coated on the surface of the bulk material, indicating that NTSP is successfully coated on the surface of the material.

[0037] The prepared Na 0.78 Mn 0.4 Co 0.1 Ni 0.2 Ti 0.1 Fe 0.1 Cu 0.1 The O2@1NTSP material was tested for EDS element distribution using a field emission scanning electron microscope. Figure 2 As shown in Figure 2, Na, Mn, Co, Ni, Ti, Fe, Cu and O are evenly distributed on the surface of the material, while Si and P are more concentrated on the surface of the particles. It can be seen that NTSP is successfully coated on the surface of the material.

[0038] To prepare Na0.78 Mn 0.4 Co 0.1 Ni 0.2 Ti 0.1 Fe 0.1 Cu 0.1 O2@1NTSP material was subjected to XRD test, and the results are as follows Figure 3 As shown. Figure 3 It can be seen that the diffraction peaks of the sample can be attributed to the P2 and O3 phase structures, proving that the material is a P2 / O3 composite phase structure material (due to the low content of NTSP, the XRD test did not detect the diffraction peak of NTSP).

[0039] The material obtained in the example was mixed with acetylene black and polyvinylidene fluoride in a mass ratio of 7:2:1, and an appropriate amount of N-methyl-2-pyrrolidone was added. The mixture was stirred to form an electrode slurry, which was then evenly coated on an aluminum foil, and the aluminum foil was placed in a vacuum oven at 110 °C and dried for 12 h. After it cooled to room temperature, a 12 mm disc-shaped electrode sheet was cut from the dried foil. The obtained electrode sheet was used as the positive electrode, metallic sodium as the negative electrode, glass fiber as the separator, and a mixed solution of 1 M NaClO4 + 95 vol% propylene carbonate + 5 vol% fluoroethylene carbonate as the electrolyte. The battery was assembled in a glove box with oxygen and water contents below 0.01 ppm to obtain a CR2025 button battery. Finally, the battery was heated to 24 mA g -1 , charge and discharge in the voltage range of 2.0-4.3 V to test its electrochemical performance. Figure 4 shown.

[0040] from Figure 4 It can be seen that Na 0.78 Mn 0.4 Co 0.1 Ni 0.2 Ti 0.1 Fe 0.1 Cu 0.1 The discharge capacity of O2@1NTSP cathode material is 105.83 mAh g -1 (a) After 300 cycles, it can still maintain 69.26 mAh g -1 The discharge capacity and capacity retention rate are 65.44% (b), which proves that the obtained material has high discharge capacity and high cycle stability.

[0041] Example 2Na 0.78 Mn 0.4 Co 0.1 Ni 0.2 Ti 0.1 Fe 0.1 Cu 0.1 Preparation of O2@2.5NTSP materials The amounts of materials in step (2) of Example 1 were adjusted to C 16 H 36 O4Ti 0.134 g, C8H 20 O4Si 0.084g, Na2CO3 0.0524g, NH4H2PO4 0.0294 g; the others remain unchanged, and the P2 / O3 composite phase Na with a NTSP coating amount of 2.5wt% is obtained. 0.78 Mn 0.4 Co 0.1 Ni 0.2 Ti 0.1 Fe 0.1 Cu 0.1 O2 material, denoted as Na 0.78 Mn 0.4 Co 0.1 Ni 0.2 Ti 0.1 Fe 0.1 Cu 0.1 O2@2.5NTSP.

[0042] The prepared Na 0.78 Mn 0.4 Co 0.1 Ni 0.2 Ti 0.1 Fe 0.1 Cu 0.1 O2@2.5NTSP material was tested by SEM, and the results are as follows Figure 5 As shown. Figure 5 It can be seen that more small particles appear on the surface of the material than in Example 1 and are coated on the surface of the bulk material. It can be seen that when NTSP increases, the surface of the material can be coated more completely.

[0043] Figure 6 For the preparation of Na 0.78 Mn 0.4 Co 0.1 Ni 0.2 Ti 0.1 Fe 0.1 Cu 0.1 XRD pattern of O2@2.5NTSP material. Figure 6 It can be seen that the diffraction peaks of the sample can be attributed to the P2 and O3 phase structures, proving that the material is a P2 / O3 composite phase structure material (due to the low content of NTSP, the XRD test did not detect the diffraction peak of NTSP).

[0044] The Na prepared by the method described in Example 1 0.78 Mn 0.4 Co 0.1 Ni 0.2 Ti0.1 Fe 0.1 Cu 0.1 O2@2.5NTSP material is used as the positive electrode material to be assembled into sodium-ion batteries. Figure 7 The prepared material has a conductivity of 24 mA g in sodium ion batteries. -1 , electrochemical performance diagram in the voltage window of 2 to 4.3 V. Figure 7 It can be seen that the first discharge specific capacity of the material is 117.83 mAh g -1 (a) After 300 cycles, it can still maintain 81.71 mAh g -1 , the capacity retention rate is nearly 70% (b), which proves that the P2 / O3 phase structure material coated with the fast ion conductor has high structural stability and excellent cycle performance.

[0045] Example 3Na 0.78 Mn 0.4 Co 0.1 Ni 0.2 Ti 0.1 Fe 0.1 Cu 0.1 Preparation of O2@5NTSP materials The amounts of materials in step (2) of Example 1 were adjusted to C 16 H 36 O4Ti 0.268 g, C8H20O4Si 0.168 g, Na2CO3 0.1048 g, NH4H2PO4 0.0588 g; the others remain unchanged, and the P2 / O3 composite phase Na with a NTSP coating of 5wt% is obtained. 0.78 Mn 0.4 Co 0.1 Ni 0.2 Ti 0.1 Fe 0.1 Cu 0.1 O2 material, denoted as Na 0.78 Mn 0.4 Co 0.1 Ni 0.2 Ti 0.1 Fe 0.1 Cu 0.1 O2@5NTSP.

[0046] The prepared Na 0.78 Mn 0.4 Co 0.1 Ni 0.2 Ti 0.1 Fe 0.1 Cu 0.1 O2@5NTSP material was tested by SEM, and the results are as follows Figure 8 As shown. Figure 8It can be seen that more small particles appear on the surface of the material than in Examples 1 and 2 and are coated on the surface of the bulk material. It can be seen that when NTSP increases, the thickness of the coating layer will also increase accordingly.

[0047] Fig. 9 For the preparation of Na 0.78 Mn 0.4 Co 0.1 Ni 0.2 Ti 0.1 Fe 0.1 Cu 0.1 XRD pattern of O2@5NTSP material. Fig. 9 It can be seen that the diffraction peaks of the sample can be attributed to the P2 and O3 phase structures, proving that the material is a P2 / O3 composite phase structure material (due to the low content of NTSP, the XRD test did not detect the diffraction peak of NTSP).

[0048] The Na prepared by the method described in Example 1 0.78 Mn 0.4 Co 0.1 Ni 0.2 Ti 0.1 Fe 0.1 Cu 0.1 O2@5NTSP material is used as the positive electrode material to be assembled into sodium-ion batteries. Fig.10 The prepared material has a conductivity of 24 mA g in sodium ion batteries. -1 , electrochemical performance diagram in the voltage window of 2 to 4.3 V. Fig.10 It can be seen that the first discharge specific capacity of the material is 108.94 mAh g -1 (a), after 300 cycles, it can still maintain 69.74% of the initial capacity (b), the results confirm that the P2 / O3 phase structure material coated with the fast ion conductor has high structural stability and excellent cycle performance.

[0049] Comparative Example P2 / O3 Composite Phase Na without Fast Ion Conductor Coating 0.78 Mn 0.4 Co 0.1 Ni 0.2 Ti 0.1 Fe 0.1 Cu 0.1 O2 Materials Prepare P2 / O3 composite phase Na according to step (1) in Example 1 0.78 Mn 0.4 Co 0.1 Ni 0.2 Ti 0.1 Fe 0.1 Cu 0.1 O2 material.

[0050] The prepared P2 / O3 composite phase Na 0.78 Mn 0.4 Co 0.1 Ni 0.2 Ti 0.1 Fe 0.1 Cu 0.1 O2 material was tested by SEM, and the results are as follows Fig.11 As shown. Fig.11 It can be seen that the surface of the material is relatively smooth and the particles have obvious edges and corners.

[0051] Fig.12 For the preparation of Na 0.78 Mn 0.4 Co 0.1 Ni 0.2 Ti 0.1 Fe 0.1 Cu 0.1 XRD pattern of O2 material. Fig.12 It can be seen that the diffraction peaks of the sample can be attributed to the P2 and O3 phase structures, and the material is a P2 / O3 composite phase structure material.

[0052] The Na prepared by the method described in Example 1 0.78 Mn 0.4 Co 0.1 Ni 0.2 Ti 0.1 Fe 0.1 Cu 0.1 O2 material is used as the positive electrode material to assemble into sodium ion batteries. Fig.13 For the preparation of Na 0.78 Mn 0.4 Co 0.1 Ni 0.2 Ti 0.1 Fe 0.1 Cu 0.1 O2 materials in sodium-ion batteries 24 mA g -1 , electrochemical performance diagram in the voltage window of 2 to 4.3 V. Fig.13 It can be seen that the first discharge specific capacity of the material is 126.3 mAh g -1 (a), the capacity retention rate after 300 cycles is 44.48% (b). The results confirm that although the P2 / O3 phase structure material without fast ion conductor coating has a higher capacity, its cycle stability is poor.

[0053] The above description is only a preferred embodiment of the present invention. All equivalent changes and modifications made according to the scope of the patent application of the present invention should fall within the scope of the present invention.

Claims

1. A fast ion conductor coated P2 / O3 composite phase layered material, characterized in that: The layered material is composed of Na5Ti2Si2PO 13 Coated in P2 / O3 composite phase Na i Mn x Co y Ni z M1 m M2 n M3 p O2 surface composition; wherein, M1 is a tetravalent metal element doped to replace the Mn position, M2 is a trivalent metal element doped to replace the Co position, and M3 is a divalent metal element doped to replace the Ni position; 0.72≤i≤0.8, 0.1≤x≤0.3, 0.1≤y≤0.4, 0.1≤z≤0.3, 0.03<m≤0.15, 0.03<n≤0.15, 0.03<p≤0.15, and x+y+z+m+n+p=1.

2. The fast ion conductor coated P2 / O3 composite phase layered material according to claim 1, characterized in that: M1 is specifically selected from one or more of Ti, Zr, and Si; M2 is specifically selected from one or more of Fe, Cr, and Al; M3 is specifically selected from one or more of Mg, Cu, and Zn.

3. The fast ion conductor coated P2 / O3 composite phase layered material according to claim 1, characterized in that: Na5Ti2Si2PO 13 In Na i Mn x Co y Ni z M1 m M2 n M3 p The coating amount of O2 surface is 1-5wt%.

4. A method for preparing a fast ion conductor coated P2 / O3 composite phase layered material as claimed in claim 1, characterized in that: First, the P2 / O3 composite layered material Na was prepared by combustion method. i Mn x Co y Ni z M1 m M2 n M3 p O2, and then coated with Na5Ti2Si2PO4 on its surface by sol-gel method. 13 .

5. The preparation method according to claim 4, characterized in that: The following steps are involved: (1) Press Na first i Mn x Co y Ni z M1 m M2 n M3 p The Na source, Mn source, Co source, Ni source, M1 source, M2 source and M3 source were weighed in a stoichiometric ratio of O2, and then stirred and mixed with sucrose and deionized water to obtain a mixed solution, and then the mixed solution was heated and stirred until it became a syrup, and then calcined at a high temperature in air to obtain a P2 / O3 composite layered material Na i Mn x Co y Ni z M1 m M2 n M3 p O2; (2) According to Na5Ti2Si2PO 13 The stoichiometric ratio of C 16 H 36 O4Ti and C8H 20 O4Si was dissolved in ethanol to obtain solution A, and Na2CO3 and NH4H2PO4 were dissolved in deionized water to obtain solution B; (3) Add P2 / O3 composite layered material Na into solution A. i Mn x Co y Ni z M1 m M2 n M3 p O2, then slowly add solution B, heat at 70 °C with stirring to evaporate to dryness, and then dry in a vacuum drying oven at 110 °C for 12 h; (4) The sample dried in step (3) is placed in a muffle furnace for calcination to obtain the P2 / O3 composite phase layered material coated with the fast ion conductor.

6. The preparation method according to claim 5, characterized in that: The Na source, Mn source, Co source, Ni source, M2 source and M3 source in step (1) are all nitrates of corresponding elements; the M1 source is one or more of titanium oxide, zirconium oxide and silicon oxide.

7. The preparation method according to claim 5, characterized in that The amount of sucrose used in step (1) is converted to 3.0 g per 1 gram of P2 / O3 composite layered material; the amount of deionized water used is converted to 38.4 mL per 1 gram of P2 / O3 composite layered material.

8. The preparation method according to claim 5, characterized in that The high temperature calcination in step (1) is to first keep the temperature at 350°C for 0.5 h, then grind in a mortar for 1 h, then heat to 500°C, keep the temperature for 3 h, and finally heat to 800-900°C, keep the temperature for 10-24 h.

9. The preparation method according to claim 5, characterized in that The calcination in step (4) is carried out at a rate of 2°C / min from room temperature to 350°C, kept at that temperature for 5 h, and then raised to 900°C and kept at that temperature for 6 h.

10. Use of the P2 / O3 composite layered material coated with the fast ion conductor material as claimed in claim 1 as a positive electrode material for a sodium ion battery.